2010
DOI: 10.1108/02652321011018332
|View full text |Cite
|
Sign up to set email alerts
|

Debit and credit card usage and satisfaction

Abstract: Purpose -This exploratory study seeks to explore the link between the choices of payment mode to customer satisfaction. It examines the Austrian market in relation to its choice and usage of debit cards versus credit cards and its impact on customer satisfaction and loyalty. Furthermore, the study aims to identify the key drivers of customer satisfaction for these two modes of electronic payment. Design/methodology/approach -A structured questionnaire was administered in person to 360 Austrian bank customers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 46 publications
2
14
0
1
Order By: Relevance
“…The payment mode literature shows that age, gender, income and education correlate positively with card ownership (Klee, 2004;Lee & Kwon, 2002;Borzekowski, Kiser, & Ahmad, 2006;Foscht, Maloles, Swoboda, & Chia, 2010). Therefore, we hypothesized that the PPM subscales are associated with these demographic factors.…”
Section: Assessing Relationship Between Ppm and Demographicsmentioning
confidence: 96%
“…The payment mode literature shows that age, gender, income and education correlate positively with card ownership (Klee, 2004;Lee & Kwon, 2002;Borzekowski, Kiser, & Ahmad, 2006;Foscht, Maloles, Swoboda, & Chia, 2010). Therefore, we hypothesized that the PPM subscales are associated with these demographic factors.…”
Section: Assessing Relationship Between Ppm and Demographicsmentioning
confidence: 96%
“…Pihak-pihak dimaksud adalah bank atau lembaga pembiayaan, merchant (pedagang), dan card holder (pemegang kartu) (Subari dan Ascarya, 2003: 41-42). (Foscht et al, 2010) Kartu debet merupakan instrumen pembayaran berbasis kartu yang pembayarannya dilakukan dengan pendebetan langsung ke rekening nasabah di bank penerbit kartu tersebut. Pada beberapa bank penerbit kartu debet terdapat kombinasi fungsi kartu debet dan kartu ATM dalam satu kartu sekaligus (kartu debet dan kartu ATM) (Subari dan Ascarya, 2003:43).…”
Section: A Kartu Kreditunclassified
“…As shown by Reference [46], it was found that a person's preference for a particular method of payment depends largely on a set of personal characteristics. Customer satisfaction is determined by both the attitude and expectations and the intrinsic performance of the financial payment instrument.…”
Section: Indicators and Expected Benefits From The Use Of Bank Cardsmentioning
confidence: 99%